2022
DOI: 10.3390/genes13101807
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Registration for High-Yielding Strain through ST and MLT of Curcuma caesia Roxb. (Jor Lab KH-2): A High-Value Medicinal Plant

Abstract: (1) Background: Curcuma caesia Roxb. is a high valued crop which is extensively used in pharmaceuticals, flavour and fragrances. C. caesia is recognised as an endangered species due to its extensive collection from the wild through human intervention. Therefore, to prevent the species from extinction, it is very necessary to conserve and cultivate this plant species for the sustainable availability of the raw material. (2) Methods: In the present plant breeding programme, a multi-year study was performed for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Significant differences among turmeric cultivars were found in yield-contributing parameters such as the number of fingers/rhizome, plant height, curcumin content, the weight of the rhizome per plant and rhizome yield in an earlier study [30]. A study conducted by Mishra et al [31] and Lal et al [32] found significant differences in the morphological traits of 135 turmeric accessions collected from different parts of India. Similarly, a separate study conducted by Akter et al…”
Section: Discussionmentioning
confidence: 96%
“…Significant differences among turmeric cultivars were found in yield-contributing parameters such as the number of fingers/rhizome, plant height, curcumin content, the weight of the rhizome per plant and rhizome yield in an earlier study [30]. A study conducted by Mishra et al [31] and Lal et al [32] found significant differences in the morphological traits of 135 turmeric accessions collected from different parts of India. Similarly, a separate study conducted by Akter et al…”
Section: Discussionmentioning
confidence: 96%
“…There are many multivariate models available for the analysis of stability. Among the various multivariate model, additive main effects and multiplicative interaction (AMMI) method and ‘GGE biplot’ are widely used ( Lal et al., 2022b ). The AMMI model is an amalgamation of the analysis of variance and the principal component analysis.…”
Section: Introductionmentioning
confidence: 99%